Autobiography of an unknown Indian - Chaudhuri, Nirad C. (Ahmedabad Jaico Publishing House, 2021)
Nirad C. Chaudhuri, Indias most controversial writer, was born at Kishorganj in East Bengal on 23rd November, 1877. Brought up in an intellectual environment, by his father a lawyer and his mother, an uncomprising Puritan, he was profoundly influenced by them in his formative years. In this autobiography he gives chapter-by-chapter account of his life: his birth place, his parents, his experiences and adventures. He talks about the race of Indian renaissance, nationalism, politics and takes us through the roads of Calcutta where he spent 32 years of his life. By writing an essay on the course of Indian History, he regards this book as a contribution to contemporary history.
Keywords: Manners and customs; Civilization